PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN SAHAM PUBLIK, DAN LIKUIDITAS TERHADAP PENGUNGKAPAN WAJIB LAPORAN KEUANGAN - Tuidza Indah Permata (Jurnal Ilmiah Wahana Akuntansi, 2013)
The purpose of this research is to examine the influence of firm size, public ownership, and liquidity on mandatory disclosure financial statement in property and real estate companies listed at Indonesian Stock Exchange during 2009-2011. The sample which is used in this research property and real estate companies listed at Indonesian Stock Exchange on period of 2009-2011. This research is using purposive sampling method to determine the sample and resulted 21 companies as research sample. Multiple regression model and statistic descriptive is used to analysis data. The result of this research shows that firm size, public ownership, and liquidity are simultaneously influence to mandatory disclosure financial statement. Firm size, public ownership, and liquidity had positive effect to mandatory disclosure financial statement. The coefficient of determination (R2) is 0,468 which indicates that the model can explain the influence of independent variables to dependent variable. Keyword : firm size, public ownership, liquidity, mandatory disclosure financial statement